Retinoblastoma: Review and new insights - Claudia Carolina Cruz-Gálvez; Juan Carlos Ordaz-Favila; Víctor Manuel Villar-Calvo; Martha Edith Cancino-Marentes; Vanessa Bosch-Canto (Frontiers in Oncology, 2022)
Retinoblastoma (Rb), the most frequent malignant intraocular tumor in childhood, is caused by mutations in the retinoblastoma gene (RB1) situated on chromosome 13q14.2. The incidence of retinoblastoma is approximately 1 in 17,000 live births with approximately 8,000 new cases diagnosed each year worldwide. Rb is the prototypical hereditary cancer in humans. Autosomal dominant inheritance is seen in 30-40% of cases whereas the non-inherited sporadic type accounts for the remaining 60-70%. Rb arises due to inactivation of both alleles of the Rb tumor suppressor gene, which results in a defective Rb protein (pRB) with subsequent cell cycle impairment and uncontrolled cell proliferation. Patients with Rb have survival rates higher than 95-98% in industrialized countries but mortality remains high in developing countries. For example, the mortality rate in Africa is 70%. In all cases of intraocular and extraocular retinoblastoma, there is a need for new therapies that are more effective and carry less risk of toxicity. The Bruckner test is a practical and easy test for the detection of Rb, this test consists of assessing the fundus reflex through the pupil (red reflex) in both eyes simultaneously with a bright coaxial light produced with the direct ophthalmoscope. Rb can be detected by the Bruckner test showing a pupil that shines white or “Leukocoria”. Although the diagnosis of Rb remains essentially clinical, the newly identified biomarkers could contribute to early molecular detection, timely detection of micrometastases and establish new therapeutic options for Rb.